2020
DOI: 10.21203/rs.3.rs-31120/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptome and metabolite profiling reveals the effects of Funneliformis mosseae on the roots of continuously cropped soybeans

Abstract: Background Arbuscular mycorrhizal fungi are the most widely distributed mycorrhizal fungi, which can form mycorrhizal symbionts with plant roots and enhance plant stress resistance by regulating host metabolic activities. In this paper, the RNA sequencing and ultra-performance liquid chromatography (UPLC) coupled with tandem mass spectrometry (MS/MS) technologies were used to study the transcriptome and metabolite profiles of the roots of continuously cropped soybeans that were infected with F. mosseae and F.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Therefore, inducing cell wall development may discourage pathogen invasion of host tissues. Other studies have shown that the inoculation of mycorrhizal fungi can also help plants alleviate the effects of biotic and abiotic stresses by regulating the development of cell wall (Lu et al, 2020;Zhang et al, 2021). In our research, we also found that the inoculation of L. bicolor could induce some cell wall pathway gene families such as expansin family, pectinesterase family and the germin-like protein subfamily.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Therefore, inducing cell wall development may discourage pathogen invasion of host tissues. Other studies have shown that the inoculation of mycorrhizal fungi can also help plants alleviate the effects of biotic and abiotic stresses by regulating the development of cell wall (Lu et al, 2020;Zhang et al, 2021). In our research, we also found that the inoculation of L. bicolor could induce some cell wall pathway gene families such as expansin family, pectinesterase family and the germin-like protein subfamily.…”
Section: Discussionsupporting
confidence: 71%
“…Mycorrhizal fungi can establish a symbiotic relationship with more than 80% of terrestrial plants, helping them absorb water and nutrients, and alleviate the negative effects of biotic or abiotic stress (Rosendahl, 2008;Santander et al, 2017). At present, it has been found that inoculation of mycorrhizal fungi can help alleviate disease on many plants such as citrus, strawberry and soybean (Lu et al, 2020). For root diseases, a large number of systematic studies have shown that mycorrhizal fungi can compete with pathogens for survival, build a hyphal network to prevent pathogens from invading roots and secrete antibacterial substances to improve the disease resistance of host plants (Abdel-Fattah & Shabana, 2002;Eke et al, 2019;Whipps, 2004;Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al (2020) reported the transcriptome change of continuously cropped strawberry in response to a soil amendment and indicated that strawberry plants reallocated defense resources to development when soil amendments alleviated the stress caused by continuous cropping. Lu et al (2020) characterized the transcriptional response of continuously cropped soybeans to Funneliformis mosseae and found that the increased activity of some disease-resistant genes may partly account for the ability of the plants to resist diseases. Our previous study indicated that the soil amendments including OM and SCPM could effectively relieve the continuous cropping obstacles to C. tangshen cultivation (Zhou et al, 2021), but the recovery mechanisms underlying this phenomenon is still remain unclear.…”
Section: Introductionmentioning
confidence: 99%